Bio monomers for green polymeric composites materials - P. M., Visakh; Bayraktar, Oguz; Menon, Gopalakrishnan, 1980- (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
'Each chapter in Bio Monomers for Green Polymeric Composites Materials presents the most recent research and technological ideas in a comprehensive style. It examines bio monomers for green polymer and the processing methods for the bio nanocomposites. It covers the preparation, characterization, and applications of bio-polymeric materials based blends, as well as the applications of biopolymeric gels in medical biotechnology. The book also explores the properties and applications of gelatins, pectins, and carrageenans gels. Additionally, it offers a plethora of information on green polymeric membranes; the bio-degradation of green polymeric composites materials; applications of green polymeric composites materials; hydrogels used for biomedical applications; and the use of natural aerogels as thermal insulations. Introduces readers to the innovative, new bio-based monomers that are taking the place of traditional petrochemical-based building blocks Covers green polymers, green composites, bio-sourced polymers, bio nanocomposites, biodegradable polymers, green polymer gels, and membranes Features input from leading researchers immersed in the area of study Bio Monomers for Green Polymeric Composites Materials is suitable for academics, researchers, scientists, engineers and advanced students in the field of bio monomers and green polymeric composites materials'--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Biomedical materials; Polymeric composites; Polymer colloids; Biofilms; Green chemistry; Monomers; Biofilms; Biomedical materials; Green chemistry; Monomers; Polymer colloids; Polymeric composites; Electronic books